The making of the slavs : history and archaeology of the Lower Danube Region, ca. 500-700 - Curta, Florin (Cambridge studies in medieval life and thought, 2001)
This book offers a new approach to the problem of Slavic ethnicity in south-eastern Europe between c. 500 and c. 700, from the perspective of current anthropological theories. The conceptual emphasis here is on the relation between material culture and ethnicity. The author demonstrates that the history of the Sclavenes and the Antes begins only at around 500 AD. He also points to the significance of the archaeological evidence, which suggests that specific artifacts may have been used as identity markers. This evidence also indicates the role of local leaders in building group boundaries and in leading successful raids across the Danube. Because of these military and political developments, Byzantine authors began employing names such as Sclavines and Antes in order to make sense of the process of group identification that was taking place north of the Danube frontier. Slavic ethnicity is therefore shown to be a Byzantine invention.--Publisher description.